Women's Health at High Altitude: An Introduction to a 7-Part Series by the International Climbing and Mountaineering Federation Medical Commission - Horakova, Lenka; Paal, Peter; Pichler Hefti, Jacqueline; Andjelkovic, Marija; Beidleman, Beth A; Derstine, Mia; Hillebrandt, David; Jean, Dominique; Mateikaitė-Pipirienė, Kastė; Rosier, Alison J; Kriemler, Susi; Keyes, Linda E (High altitude medicine & biology, 2023)
Horakova, Lenka, Peter Paal, Jacqueline Pichler Hefti, Marija Andjelkovic, Beth A. Beidleman, Mia Derstine, David Hillebrandt, Dominique Jean, Kastė Mateikaitė-Pipirienė, Alison J. Rosier, Susi Kriemler, and Linda E. Keyes. Women's health at high altitude: An introduction to a 7-part series by the International Climbing and Mountaineering Federation Medical Commission. High Alt Med Biol. 24:243-246, 2023. Background: Women have been traveling to high altitude since the inception of modern mountaineering. Although there are distinct female-specific features such as menstruation and menopause relevant to adaptation to and performance at high altitude, very little data exist on women's high-altitude health. To summarize what is known to date, the Medical Commission of the International Climbing and Mountaineering Federation (UIAA) has created a series of articles on women's health, high altitude illness, and performance at high altitude. Methods: Assembling an international author team, two types of manuscripts were developed: (1) reviews on female-specific topics such as pregnancy; (2) reviews on sex differences in high-altitude related illnesses, nutrition, cold injuries, and mortality. Results: The literature search yielded 7,165 articles, with 482 studies meeting the inclusion criteria for full-text review. The authors of individual chapters reviewed these articles and performed additional hand searches. Conclusions: Some important questions on women sojourning and exercising at high altitude have been studied, but many are still awaiting a qualified and evidence-based response. Our seven reviews, to be published in future issues of this journal, summarize what is known about lowland women sojourning at high altitude, provide recommendations, and highlight knowledge gaps in high altitude women's medicine.
Keywords: nadmořská výška; Women's Health; výšková nemoc; zdraví žen; ruka; Altitude Sickness; lidé; Female; mužské pohlaví; Altitude; Pregnancy; Male; Mountaineering; těhotenství; Hand; ženské pohlaví; horolezectví; Humans